Zoledronic acid add-on therapy for standard-risk Ewing sarcoma patients in the Ewing 2008R1 trial - Koch, Raphael; Haveman, Lianne; Ladenstein, Ruth; Brichard, Benedicte; Jürgens, Heribert; Cyprova, Sona; van den Berg, Henk; Hassenpflug, Wolf; Raciborska, Anna; Ek, Torben; Baumhoer, Daniel; Egerer, Gerlinde; et al. (Clinical cancer research, 2023)
The phase III, open-label, prospective, multicenter, randomized Ewing 2008R1 trial (EudraCT2008-003658-13) was conducted in 12 countries to evaluate the effect of zoledronic acid (ZOL) maintenance therapy compared with no add-on regarding event-free survival (EFS, primary endpoint) and overall survival (OS) in standard-risk Ewing sarcoma (EWS).Eligible patients had localized EWS with either good histologic response to induction chemotherapy and/or small tumors (<200 mL). Patients received six cycles of VIDE induction and eight cycles of VAI (male) or eight cycles of VAC (female) consolidation. ZOL treatment started parallel to the sixth consolidation cycle. Randomization was stratified by tumor site (pelvis/other). The two-sided adaptive inverse-normal four-stage design (planned sample size 448 patients, significance level 5%, power 80%) was changed after the first interim analysis using the Müller-Schäfer method.Between April 2010 and November 2018, 284 patients were randomized (142 ZOL/142 no add-on). With a median follow-up of 3.9 years, EFS was not significantly different between ZOL and no add-on group in the adaptive design (HR, 0.74; 95% CI, 0.43-1.28, P = 0.27, intention-to-treat). Three-year EFS rates were 84.0% (95% CI, 77.7%-90.8%) for ZOL vs. 81.7% (95% CI, 75.2%-88.8%) for no add-on. Results were similar in the per-protocol collective. OS was not different between groups. The 3-year OS was 92.8% (95% CI, 88.4%-97.5%) for ZOL and 94.6% (95% CI, 90.9%-98.6%) for no add-on. Noticeable more renal, neurologic, and gastrointestinal toxicities were observed for ZOL (P < 0.05). Severe renal toxicities occurred more often in the ZOL arm (P = 0.003).In patients with standard-risk localized EWS, there is no additional benefit from maintenance treatment with ZOL.
Gesehen am 02.07.2024